2022
DOI: 10.17344/acsi.2022.7680
|View full text |Cite
|
Sign up to set email alerts
|

The Paramagnetic or Spin Crossover Iron(III) Complexes Based-on Pentadentate Schiff Base Ligand: Crystal Structure, and Magnetic Property Investigation

Abstract: A series of bi- or mononuclear hexacoordinate iron(III) complexes, [Fe(L)][Fe(bpb)(CN)2]·CH3OH·0.5H2O (1), [Fe(L)] [Co(bpb)(CN)2]·CH3OH (2) [(Fe (L))2(4,4’-bipy)](BPh4)2 (3), [Fe(L)(py)](BPh4) (4) and [Fe(L)(dmap)](BPh4) (5) (bpb = 1,2-bis(pyridine-2-carboxamido)benzenate, L = N,N’-bis(2-hydroxybenzyliden)-1,7-diamino-4-azaheptane, dmap = 4-dimethylaminopyridine), have been prepared with the pentadentate Schiff base iron(III) compound as assemble precursor and characterized by element analysis, IR and X-ray di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…[31] Subsequently Xu et al synthesized complexes [Fe(L)(py)] and [Fe(L)(dmap)](BPh 4 ) (L = N,N'-bis(2-hydroxybenzyliden)-1,7-diamino-4-azaheptane; dmap = 4-dimethylaminopyridine) using pentadentate Schiff base ligands and pyridine like ligands. [32] The magnetic studies have revealed thermally induced gradually complete SCO behaviour at different temperatures. These studies emphasize the important role of Fe(III) and pentadentate Schiff base ligands in spin-crossover behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Subsequently Xu et al synthesized complexes [Fe(L)(py)] and [Fe(L)(dmap)](BPh 4 ) (L = N,N'-bis(2-hydroxybenzyliden)-1,7-diamino-4-azaheptane; dmap = 4-dimethylaminopyridine) using pentadentate Schiff base ligands and pyridine like ligands. [32] The magnetic studies have revealed thermally induced gradually complete SCO behaviour at different temperatures. These studies emphasize the important role of Fe(III) and pentadentate Schiff base ligands in spin-crossover behaviour.…”
Section: Introductionmentioning
confidence: 99%